Auto-Tune: Efficient Autonomous Routing for Payment Channel Networks - Hong, Hsiang-Jen; Chang, Sang-Yoon; Zhou, Xiaobo (2022 IEEE 47th Conference on Local Computer Networks (LCN), 2022)
Payment Channel Network (PCN) is a scaling solution for Cryptocurrency networks. We advance the practicality of the PCN multi-path routing by better modeling the system to incorporate the cost of routing fee and the privacy requirement of the channel balance. We design our Auto-Tune algorithm to optimize the routing concerning both the success rate and the routing fee and utilizing the limited channel capacity information (due to the privacy of the PCN user, the channel balance information is withheld). The simulation result shows Auto-Tune outperforms the current PCN implementation based on single-path routing in the success rate. We compare Auto-Tune against the state-of-the-art Flash algorithm, utilizing the channel-balance information, violating the PCN user privacy, and diverging from current implementation practices. Auto-Tune achieves the routing fee close to the optimal fee obtained by Flash, and its success rate is also close to the success rate achieved by Flash.